MIDWIFERY CARE FOR PREGNANT WOMEN, Mrs. F IN LAMPEUNEURUT VILLAGE, SUB-DISTRICT DARUL IMARAH, THE DISTRICT OF ACEH BESAR IN 2026: Midwifery Care for Pregnant Women - Fanny Rahma; Adri Idiana; Yuni Sari (Department of Midwifery, Health Polytechnic of Aceh, 2026)
Introduction: Maternal Mortality Rate (MMR) remains a global health problem that is largely preventable through quality and continuous midwifery care. The main causes of maternal death in Indonesia include bleeding, preeclampsia/eclampsia, and infection, so that routine pregnancy monitoring through home visits is an important strategy in early detection of complications. This case report aims to provide midwifery care for Mrs. F and document it in midwifery documentation. Method: Care was provided to Mrs. F, 40 years old, G2P1A0, with a history of cesarean section, through three visits at the patient's home. at a gestational age of 26 weeks 4 days to 30 weeks 4 days. Result: Subjective data showed that the mother complained of fatigue, lower abdominal cramps accompanied by dizziness, and back pain. The results of the objective examination showed that the mother's general condition was good, with normal vital signs, and a transverse fetal position at 28 weeks 4 days of gestation, which returned to normal after knee and chest position exercises. The care provided included education on second- and third-trimester pregnancy discomforts, maternal nutrition, anemia prevention, knee-chest exercises, pregnancy danger signs, childbirth preparation, postpartum contraception, and Early Initiation of Breastfeeding (IMD). Conclusion: The care results showed that the mother's and fetus's conditions remained within normal limits, and the mother understood all counseling provided. Discussion: Comprehensive and continuous midwifery care through home visits is expected to support a healthy pregnancy and prevent complications.